The elephant in the room: understanding the pathogenesis of Charles Bonnet syndrome. (8th October 2019) - Carpenter, Kilda; Jolly, Jasleen K; Bridge, Holly
Abstract: Purpose: Charles Bonnet syndrome (CBS) is a syndrome characterised by complex visual hallucinations in individuals who are cognitively normal, though often elderly and visually impaired. Although first described over 250 years ago, the condition remains poorly understood and difficult to treat. Recent findings: Our understanding of CBS pathogenesis has advanced little since it was first described, and much of the recent literature consists of case studies strikingly similar to the first published account of CBS. However, imaging studies have provided some indication as to the cortical areas implicated in the genesis of complex visual hallucinations, and the existence of similar hallucinatory syndromes in other sensory modalities suggests a common underlying mechanism. Summary: This review begins by describing what is currently known about CBS, focusing on epidemiology, clinical presentation and diagnosis. It then explores potential starting points for better understanding the pathogenesis of CBS, namely the existence of similar conditions in other sensory modalities and the reproduction of complex visual hallucinations in sensory deprivation scenarios. Finally, it discusses how CBS should be approached in clinical practice.